PENGARUH LEADER MEMBER EXCHANGE DAN MOTIVASI BERPRESTASI TERHADAP KOMITMEN AFEKTIF PADA PEGAWAI SEKTOR JASA PENDIDIKAN KOTA BANDUNG - Aan Hardiyana; Vicky Achmad Zulfikar; Rd. Okky Satria; Kadir Kadir; R. Deni Purana (STMIK Mardira Indonesia, Bandung, 2021)
This study aims to determine the effect of Leader-Member Exchange (LMX) and achievement motivation on affective commitment to employees of the education service sector in Bandung. Previous research has shown that delegative leadership consisting of competency readiness, quality of time together, suitability of goals, level of job position, and quality of superior-subordinate relationship (LMX) has affected achievement motivation and continuous commitment. However, after more profound analysis of partial parameters, it turns out that only job position and LMX affect achievement motivation significantly, and only in terms of goal compatibility significantly affect continuance commitment. This situation demands to conduct further research on leadership. On the other hand, previous research shows that LMX does not significantly affect continuance commitment. Therefore, the affective commitment chose to investigate whether it will be significantly affected and improved by LMX simultaneously and partially with parameters. Therefore, achievement motivation was selected and appointed as the focus of research to find out and analyze its effect more deeply on the affective commitment that previous researchers had developed. As a result, there is a significant direct effect of LMX on the affective commitment by 17.2%. Furthermore, there is an indirect effect of LMX through achievement motivation on the affective commitment of 12.3%, so the total direct and indirect effect of LMX on affective commitment is 29.6%. Likewise, there is a significant direct effect of achievement motivation on the affective commitment by 23.8%, and there is an indirect effect of achievement motivation through LMX on the affective commitment of 12.3% so that the total direct and indirect effect of achievement motivation on affective commitment is equal to 36.1%. Then the total effect of LMX and achievement motivation on affective commitment is 65.7%. So, if LMX and achievement motivation are more effective on the job, it will increase affective commitment. Keywords : Leader-Member Exchange, Achievement Motivation, Affective Commitment.